Implementasi of Triage on the Role Attitude of Emergency Instalation Nurses - Rahmawati, Agustini Liviana Dwi; Rosida, Rosida; Saputra, M. Khalid Fredy; Zaenal, Zaenal; Pella, Yosin Herloheti; Mahoklory, Serly Sani; Ervan, Ervan (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Triage is a process to determine which patients should receive treatment first based on the severity of the injury or illness. In triage, patients are grouped into 6 categories, blue label, red label, yellow label, green label, white label, and black label. The highest priority is patients with emergency conditions accompanied by disturbances in the airway, breathing, circulation, which are labeled in blue. The second priority is patients with emergency conditions, which are labeled in red. The third priority is given to patients with minimal emergency conditions, which are labeled in yellow. The next priority is cases without emergencies, but if they are not treated immediately they will have a negative impact on the patient, which is labeled in green. The next priority is the white label given to patients whose conditions are not serious, not emergency, and do not require immediate treatment. Last priority is given to patients who died or had serious irreversible injuries who were labeled in black. The purpose of this study was to determine the relationship between the roles and attitudes of emergency room nurses and the implementation of triage based on priority. The research method used is descriptive correlational with cross sectional design. The results showed that the majority of the role of nurses was good with the implementation of triage as many as 25 people (65.8%), the majority of positive attitudes with the implementation of triage as many as 23 people (60.5%) and the majority carried out triage according to SOP as many as 30 people (78.9%) . The results of the study with the chi-square test p-value <0.05. In conclusion, there is a relationship between the role and attitude of the emergency room nurse and the implementation of triage based on priority.